Proto-Slavic *kŭrkŭ: Semantics and Etymology - Mikhail N. Saenko (Slovene, 2021)
The article is devoted to the semantics of the Proto-Slavic word *kъrkъ, whose descendants have a wide range of meanings from ‘throat’ to ‘back’. The analysis presented shows that the Proto-Slavic word can be most probably reconstructed to mean ‘vertebra prominens / cervical vertebrae’. With this taken into account, the author looks at the previously proposed etymologies and puts forward a new one.